2D piezotronics in atomically thin zinc oxide sheets: Interfacing gating and channel width gating. (June 2019) - Wang, Longfei; Liu, Shuhai; Zhang, Zidong; Feng, Xiaolong; Zhu, Laipan; Guo, Hengyu; Ding, Wenbo; Chen, Libo; Qin, Yong; Wang, Zhong Lin
Abstract: Piezotronics has potential applications in human-machine interfacing, smart skin and robotics. Here, we report the first study of two-dimensional (2D) piezotronics based on atomically thin ZnO sheets. Using the inner crystal out-of-plane potential generated by the piezoelectric polarization charges created at atomically thin ZnO surfaces under stress/strain to simultaneously modulate the metal-ZnO Schottky barrier height and the conductive channel width of ZnO, the electronic transport processes in the two-terminal devices are effectively tuned by external mechanical stimuli. Moreover, the thickness dependence of 2D piezotronics is investigated to deeply explore the inner tuning mechanism. As decreasing the thickness of ZnO from tens of nanometre to atomic scale, the gauge factor is improved to ∼2 × 10 8 . The strain sensitivity is enhanced by over three orders of magnitude owing to the increased effective piezoelectric polarizations, which is in contrast to the conventional field effect transistor with the reduce of channel lengths. This study presents in-depth understandings about the 2D piezotronics in both interfacing gating and channel width gating in piezotronics, which fundamentally paves a way for applying 2D materials with out-of-plane piezoelectricity and semiconducting property in next generation of electromechanical nanodevices. Graphical abstract: 2D piezotronics in atomically thin ZnO sheets are explored for the first time by using inner crystal out-of-plane piezopotential in 2D materials as 'gate' controlling signal to simultaneously modulate the interface barrier and the conductive channel width, and further tune the electronic processes, which presents in-depth understandings about the 2D piezotronics in both interfacing gating and channel-width gating in piezotronics.Image 1 Highlights: 2D piezotronics based on atomically thin ZnO sheets is reported for the first time. The inner tuning mechanism of the thickness dependence of 2D piezotronics is explored deeply in both interfacing gating and channel width gating. As the thickness of ZnO decreases from tens of nanometre to atomic scale, the strain sensitivity is enhanced by over three orders of magnitude.